2021
DOI: 10.1155/2021/6648779
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Childhood Abuse, Resilience, Mindfulness, and Waterpipe Smoking: Implications for Cessation Interventions

Abstract: Introduction. Recent research has established a link between childhood abuse and later drug abuse. For waterpipe smoking (WPS), such a role has not been adequately clarified. Aims. To explore the mediating effect of resilience and mindfulness on the association between childhood abuse and current WPS among college students. Methods. A cross-sectional study was conducted among a consecutive sample ( n = 776 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, studies demonstrated that physical and psychological abuse would increase the possibility of marijuana and alcohol consumption among youth (45) and waterpipe smoking (46).…”
Section: The Effect Of Adverse Childhood Experiencesmentioning
confidence: 99%
“…Moreover, studies demonstrated that physical and psychological abuse would increase the possibility of marijuana and alcohol consumption among youth (45) and waterpipe smoking (46).…”
Section: The Effect Of Adverse Childhood Experiencesmentioning
confidence: 99%